Cover Image, Volume 139, Issue 30. Issue 30 (1st July 2022) - Sarath, Pampayil Sasikumar; Thomas, Sabu; Haponiuk, Józef T.; George, Soney C.
Abstract : This cover image designed by Sarath P.S. in consultation with Dr. Soney C. George features a Silicone rubber (QM) loaded with silane modified graphene oxide (SiGO) that exhibits superior mechanical, thermal, and tribological capabilities. The lubricating effect of graphene oxide played a major role in improving the tribological features of QMSiGO composites. The friction coefficient is dramatically reduced when SiGO is added, largely due to the creation of a lubricant film that smooths the material surfaces and reduces frictional heat, lowering the COF and specific wear rate. DOI: 10.1002/app.52299